Dialética e decadência – Lukács e a crítica da filosofia contemporânea - Cannalonga, Francisco Malê V (2025)
The purpose of the present work is the exploration of Lukács' critique of contemporary philosophy, especially philosophical irrationalism. We believe that this critique cannot be reduced to a polemic with a political slant, but rather it constitutes a confrontation of great theoretical rigor and analytical fruitfulness. We shall take as our point of departure Lukács’ “theory of ideological decay”, which seeks to delineate the fundamental tendencies of bourgeois thought from 1848 onwards, and then seek to understand how these tendencies crystallize in conceptual form in philosophical thought, giving rise to a basic ontology of bourgeois thought. After this preliminary investigation, we will try to address the way in which Lukács’ analysis offers useful instruments for analyzing the problems relating to the genesis of contemporary philosophy and the constitution of philosophical irrationalism grounded on the theoretical-ideological premises identified by Lukács’ “theory of ideological decay”